Automatic load level follow-up of forwarders' fuel and time consumption. Issue 3 (1st September 2016) - Manner, Jussi; Nordfjell, Tomas; Lindroos, Ola
ABSTRACT: Automatic collection of forwarding follow-up data has recently become possible. The objective of this study was to obtain representative values of fuel consumption for large forwarders in final felling operations. Since fuel consumption is dependent on time consumption, speed, and total driven distance, these variables were also included in the study. The study explored data collected and presented by John Deere forwarders' conventional on-board computers (TimberLink). Nine operators forwarded 15, 329 loads, in total, at sites with representative terrain conditions for large parts of mid-Sweden. A limitation with the used dataset was that load-sizes (e.g. volume or mass) were not available. The median driven distance was 670 m/load, and median total fuel consumption was 8.5 l/load or 12.4 l/km. Typically, Driving only and Crane work only accounted for most of the fuel consumption (50 and 40%, respectively). Median forwarding time was 43.1 minutes/load at average speeds of 2.2–3.3 km/h. Fuel consumption, time consumption and total driven distance were clearly correlated. Standard TimberLink data were found to be intuitively logical and to provide results consistent with current literature. It enabled gathering of high resolution fuel consumption data during whole years of work. However, elucidating main and interactive effects of predictive variables and operator behavior on fuel and time consumptions is challenging, and requires more detailed information about loads (e.g. volumes and numbers of assortments) and stand conditions (e.g. log concentrations and terrain conditions) than provided in this study.